2012
DOI: 10.5120/5717-7778
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Phase Locked Loop based System for Nakagami -m fading Channel Model

Abstract: The modified structure of a Digital Phase Locked Loop (DPLL) based systems for dealing with Nakagami-m fading is proposed here. The emphasis of the work is to generate input signal under various fading conditions with certain modulation transmitted through Nakagami-m channels and to evaluate the performance of the proposed DPLL in terms of Bit Error Rate (BER). Statistical characteristics of the faded input signal have been evaluated in terms of Probability Distribution Function (PDF), Level Crossing Rate (LCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The modified structure of a Digital Phase Locked Loop (DPLL) based carrier detection systems for dealing with Nakagami-m fading has already been proposed [1]. BER performance of the DPLL under varied fading conditions using Nakagami -m fading model, QPSK modulation and uncoded channel have been reported to be comparable to the performance of the existing systems of similar type.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The modified structure of a Digital Phase Locked Loop (DPLL) based carrier detection systems for dealing with Nakagami-m fading has already been proposed [1]. BER performance of the DPLL under varied fading conditions using Nakagami -m fading model, QPSK modulation and uncoded channel have been reported to be comparable to the performance of the existing systems of similar type.…”
Section: Introductionmentioning
confidence: 85%
“…It has two inputs, the frequency count of local reference signal and the other one is the incoming input signal. We have found that the sixth order polynomial fitting can generate a good estimate of the QPSK modulated sinusoid signal under effect of additive noise and multipath path fading channel [1,2].…”
Section: Proposed Digital Phase Locked Loop Based System For Carmentioning
confidence: 99%
“…Rayleigh and Rician fading models provide accurate estimates of the wireless fading environment prevelant in urban, sub-urban and rural areas [5,7]. The proposed Parallel PFD based modified DPLL system is tested under degraded effects of Rayleigh and Rician fading.…”
Section: Rayleigh and Rician Fading Modelmentioning
confidence: 99%
“…where a k is the gain in the k th path, Ȧ c is the angular carrier frequency for transmission, Ȧ dk is the Doppler Frequency due to relative motion in between the transmitter and receiver for k th path and k is the random phase for the k th path [2,5].…”
Section: Rayleigh and Rician Fading Modelmentioning
confidence: 99%
See 1 more Smart Citation